Effectiveness and safety of dabigatran therapy in daily-care patients with atrial fibrillation - Beyer-Westendorf, Jan; Ebertz, Franziska; Förster, Kati; Gelbricht, Vera; Michalski, Franziska; Köhler, Christina; Werth, Sebastian; Endig, Heike; Pannach, Sven; Tittl, Luise; Sahin, Kurtulus; Daschkow, Katharina; Weiss, Norbert (Thrombosis and Haemostasis, 2015)
The effectiveness and safety of dabigatran for stroke prevention in atrial fibrillation (SPAF) demonstrated in RE-LY needs to be confirmed in daily care. To evaluate treatment persistence, effectiveness and safety of dabigatran therapy in SPAF patients in daily care, we used data from an ongoing, prospective, non-interventional registry of more than 2,500 patients on novel oral anticoagulants in daily care. Between October 1, 2011 and February 28, 2013, a total of 341 SPAF patients receiving dabigatran were enrolled. The combined endpoint of stroke/transient ischaemic attack/systemic embolism occurred at a rate of 2.93/100 patient-years in the intention-to-treat analysis (95%-CI 1.6–4.9) and at 1.9/100 patient-years in the on treatment analysis (events within three days after last intake). On-treatment rates were higher in patients selected for 110 mg dabigatran (n=183) BID compared to the 158 patients selected for 150 mg BID (2.88 [95% CI 1.16–5.93] vs 0.86/100 patient-years [95% CI 0.10, 3.12]). On treatment, major bleeding occurred at a rate of 2.3/100 patient-years and numerically more often in patients receiving the 110 mg BID dose compared to the 150 mg BID dose (2.9 vs 1.7/100 patient-years). Dabigatran treatment discontinuation occurred in a total of 124 patients during follow-up (25.8 per 100 patient-years in Kaplan Meier analysis). Main reasons for treatment discontinuation were nonbleeding side effects. Our data contribute to the confirmation of effectiveness and relative safety of dabigatran in unselected patients in daily care. However, discontinuation rates are not lower than those reported for patients treated with vitamin K antagonists.
Keywords: Anticoagulation; atrial fibrillation; bleeding; dabigatran